A Student-friendly Framework for Adaptive 3D-Virtual Learning Environments : A Student-friendly Framework for Adaptive 3D-Virtual Learning Environments - Alam, Aftab; Ullah, Sehat; Ali, Numan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Three dimensional virtual learning environments (3D-VLEs) with adaptive capability have made the learning process easy and closer to one-to-one tutoring. These systems have the ability to dynamically adapt to the learning capability of students and all the activities they perform, which results in improved learning. In this paper, we present a method for defining the adaptive aspect of 3D-VLEs where student learning is quantitatively measured. The contents of 3D-VLEs are changed according to the learning skill of students. A weak learner is provided more time to complete a given learning module while a good learner can finish his work in less time. As a result students become motivated towards learning. The proposed method is student friendly and it enhances the learning capability of the students by providing them learning materials which they can absorb. The experimental results show the effectiveness of our proposed approach for 3D-VLEs.